2006
DOI: 10.1080/13547860600764245
|View full text |Cite
|
Sign up to set email alerts
|

Testing Twin Deficits Hypothesis using VARs and Variance Decomposition

Abstract: This paper examines the twin deficits hypothesis in Indonesia, Malaysia, the Philippines and Thailand (ASEAN-4 countries). The major findings of this paper are: (1) Long run relationships are detected between budget and current account deficits. (2) We found that the Keynesian reasoning fits well for Thailand since a unidirectional relationship exists which runs from budget deficit to current account deficit. For Indonesia the reverse causation (current account targeting) is detected while the empirical result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 48 publications
0
30
0
5
Order By: Relevance
“…Their findings suggest that the correlation between two deficits is complex and ambiguous and it is subject to change depending on the underlying tax system, trade patterns and barriers, the exchange rate, etc. Baharumshah et al (2006) examine the TDH for Indonesia, Malaysia, the Philippines and Thailand and find that the Keynesian reasoning fits well for Thailand since a unidirectional relationship exists that runs from budget deficit to current account deficit. For Indonesia, the reverse causation (current account targeting) is detected while the empirical results indicate that a bi-directional pattern of causality exists for Malaysia and the Philippines.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Their findings suggest that the correlation between two deficits is complex and ambiguous and it is subject to change depending on the underlying tax system, trade patterns and barriers, the exchange rate, etc. Baharumshah et al (2006) examine the TDH for Indonesia, Malaysia, the Philippines and Thailand and find that the Keynesian reasoning fits well for Thailand since a unidirectional relationship exists that runs from budget deficit to current account deficit. For Indonesia, the reverse causation (current account targeting) is detected while the empirical results indicate that a bi-directional pattern of causality exists for Malaysia and the Philippines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The connection between the budget deficit and current account deficit can be derived from the national account identity: 1 Baharumshah and Lau (2006) investigate twin deficits for a panel of South East Asian Central Banks (SEACEN) countries including Sri Lanka and consider the role of the two financial variables. However, as the investigation is based on panel data analysis, they do not explicitly provide evidence for Sri Lanka.…”
Section: Theoretical Underpinnings Of Twin Deficit Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…He concluded that twin-deficits theory holds in the short-run, but not in the long run for India. Baharumshah, et al (2006) examined the twin deficit hypothesis in Indonesia, Malaysia, the Philippines and Thailand using co-integration, impulse response function and variance decomposition of the VAR model. Their study found long run relationships between budget and current account deficits.…”
Section: Methodological and Empirical Reviewmentioning
confidence: 99%
“…In another study, Baharumshah, Lau, Khalid (2006) examined how fiscal and current account deficits were affected by interest and nominal exchange rates in Asia. Data from 1976 to 2000 of 4 countries (Philippines, Indonesia, Malaysia, and Thailand) were analysed by the Johansen co-integration test.…”
Section: Empirical Literaturementioning
confidence: 99%